2018
DOI: 10.3390/ijms19082226
|View full text |Cite
|
Sign up to set email alerts
|

mTOR-Related Brain Dysfunctions in Neuropsychiatric Disorders

Abstract: The mammalian target of rapamycin (mTOR) is an ubiquitously expressed serine-threonine kinase, which senses and integrates several intracellular and environmental cues to orchestrate major processes such as cell growth and metabolism. Altered mTOR signalling is associated with brain malformation and neurological disorders. Emerging evidence indicates that even subtle defects in the mTOR pathway may produce severe effects, which are evident as neurological and psychiatric disorders. On the other hand, administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 264 publications
(334 reference statements)
4
91
0
3
Order By: Relevance
“…It suggests that 5‐HT 6 receptor antagonists, which recently failed in Phase III clinical trials as symptomatic treatment of cognitive symptoms in Alzheimer's disease (Atri et al , ; Khoury et al , ), might be repositioned as “disease‐modifying” treatment to prevent emergence of cognitive deficits in adolescent cannabis abusers. Such a strategy based on early administration of 5‐HT 6 receptor antagonists is certainly more relevant than mTOR blockade by pharmacological inhibitors, as it will specifically prevent the non‐physiological activation of prefrontal mTOR without affecting physiological cerebral mTOR activity, which plays a key role in numerous physiological processes such as synaptic plasticity (Bockaert & Marin, ; Younts et al , ; Switon et al , ; Ryskalin et al , ). Accordingly, 5‐HT 6 receptor antagonism will not reproduce the severe side effects induced by mTOR inhibitors such as rapamycin, which limit their clinical development for the treatment of psychiatric diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that 5‐HT 6 receptor antagonists, which recently failed in Phase III clinical trials as symptomatic treatment of cognitive symptoms in Alzheimer's disease (Atri et al , ; Khoury et al , ), might be repositioned as “disease‐modifying” treatment to prevent emergence of cognitive deficits in adolescent cannabis abusers. Such a strategy based on early administration of 5‐HT 6 receptor antagonists is certainly more relevant than mTOR blockade by pharmacological inhibitors, as it will specifically prevent the non‐physiological activation of prefrontal mTOR without affecting physiological cerebral mTOR activity, which plays a key role in numerous physiological processes such as synaptic plasticity (Bockaert & Marin, ; Younts et al , ; Switon et al , ; Ryskalin et al , ). Accordingly, 5‐HT 6 receptor antagonism will not reproduce the severe side effects induced by mTOR inhibitors such as rapamycin, which limit their clinical development for the treatment of psychiatric diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that ß-glucan treatment induces activation of the dectin-1/ Akt/PTEN/mTOR/HIF-1α signaling pathway in innate immune cells [21]. That is, β-glucan activates dectin-1 which recruits Akt, leading to activation of mammalian target of rapamycin (mTOR) with suppression of PTEN expression and phosphorylation of the tuberous sclerosis complex (TSC) [22]. Activation of this pathway switches cellular metabolism from oxidative phosphorylation (ATP synthesis) to glycolysis, thereby reducing basal cellular respiration and increasing in glucose consumption, resulting in higher production of lactate [21].…”
Section: Mechanisms Of Trained Immunitymentioning
confidence: 99%
“…Mammalian target of rapamycin (mTOR) is an integrated multi-protein serine-threonine kinase complex, existing in two functional forms of mTORC1 and mTORC2, which can be activated, among others by growth factors (insulin, insulin-like growth factor IGF-1), stress (DNA damage, decrease in blood glucose, and oxygen), amino acids such as leucine (Leu) and arginine (Arg), as well as high ATP levels [58][59][60][61]. Activation of each form of the complex is closely related to stimulation of the PI3K/PTEN/AKT/mTOR tyrosine kinase pathway, which hence linked to synthesis, autophagy, lipogenesis, ketogenesis, mitochondrial function, glucose uptake, as well as insulin signaling via the transmembrane receptor tyrosine kinase (RTK) [62,63]. The mTOR pathway controlling neurogenesis, synaptogenesis, cell proliferation, autophagy, and apoptosis, becomes a very important signaling pathway, whose disorder leads to serious consequences and is considered an important etiological factor of schizophrenia.…”
mentioning
confidence: 99%